2021
DOI: 10.1093/treephys/tpaa176
|View full text |Cite
|
Sign up to set email alerts
|

Previous drought exposure leads to greater drought resistance in eucalypts through changes in morphology rather than physiology

Abstract: Over their lifetime, trees are repeatedly exposed to droughts. It is therefore important to understand if repeated drought exposure makes trees more or less drought tolerant. Here, we investigated the effect of repeated droughts on functional trait expression and tree function in Eucalyptus obliqua. Further, we tested whether previous drought exposure enabled trees to avoid leaf death for longer under a subsequent severe drought. Trees were subjected for one year to two drought-rewatering cycles (drought treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Furthermore, long-term drought preconditioning appears to have enhanced the physiological vigor of western larch seedlings, as water limitation increased the mass, count, and length of new roots produced during aeroponic growth (none of which were strongly correlated with initial lateral root mass). These results agreed with those of Pritzkow et al (2021) , who subjected seedlings of Eucalyptus obliqua to long-term drought preconditioning and found that preconditioning induced drought-adaptive reductions in foliar biomass. Pritzkow et al (2021) reported that drought preconditioning did not influence plant water-relations or anatomy, but the smaller aboveground mass of preconditioned seedlings was associated with reduced water use and increased seedling survival under dry outplanting conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, long-term drought preconditioning appears to have enhanced the physiological vigor of western larch seedlings, as water limitation increased the mass, count, and length of new roots produced during aeroponic growth (none of which were strongly correlated with initial lateral root mass). These results agreed with those of Pritzkow et al (2021) , who subjected seedlings of Eucalyptus obliqua to long-term drought preconditioning and found that preconditioning induced drought-adaptive reductions in foliar biomass. Pritzkow et al (2021) reported that drought preconditioning did not influence plant water-relations or anatomy, but the smaller aboveground mass of preconditioned seedlings was associated with reduced water use and increased seedling survival under dry outplanting conditions.…”
Section: Discussionsupporting
confidence: 91%
“…These results agreed with those of Pritzkow et al (2021) , who subjected seedlings of Eucalyptus obliqua to long-term drought preconditioning and found that preconditioning induced drought-adaptive reductions in foliar biomass. Pritzkow et al (2021) reported that drought preconditioning did not influence plant water-relations or anatomy, but the smaller aboveground mass of preconditioned seedlings was associated with reduced water use and increased seedling survival under dry outplanting conditions. The present study established that long-term drought preconditioning of western larch promotes the development of seedling traits associated with establishment success in dry field conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The observed limitations of hydraulic function and foliage development undoubtedly have serious consequences for trees. Importantly, reduced foliation and partial branch dieback may also serve as a post‐drought acclimation response that rebalances root water uptake and transpirational water loss through canopies over longer developmental timescales (Rood et al ., 2000; Bréda et al ., 2006; Trugman et al ., 2018; Pritzkow et al ., 2021). This is in good agreement with recent studies linking observations of heterogeneous leaf or branch mortality across the canopy of drought‐stressed trees with hydraulic dysfunction, and based on this, partial leaf or branch mortality has been proposed to act as buffer against complete dehydration and tree death during prolonged drought (Davis et al ., 2002; Cardoso et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The world's dryland areas are predicted to become increasingly arid, with worsening droughts (IPCC, 2021), which reduce vegetation cover and can permanently alter habitat structure (Pritzkow et al, 2021). At our study site, densely leaved, green shrubs-identified as critical thermal refuges in other terrestrial habitats (Carroll et al, 2015;Anthony et al, 2020;Ruth et al, 2020)-were simply not present during the data collection period due to 2 years of severe drought.…”
Section: Climate Change and Adaptation Managementmentioning
confidence: 87%
“…In previous summers, we had observed many small passerines (although not Jacky Winters) sheltering within such shrubs at high temperatures. The loss of this microhabitat, combined with the reduction in leaf area that eucalypts suffer during drought (Pritzkow et al, 2021), is likely to seriously impair the ability of avian species to survive heat wave events.…”
Section: Climate Change and Adaptation Managementmentioning
confidence: 99%